Legal Position of Awig –Awig in the National Legal System as a Source of Law (Written Customary Law) - adhitya widya kartika; Wiwin Yulianingsih; Yana Indawati (Veteran Justice Journal, 2020)
Village is the smallest part of the state structure. A number of villages in Indonesia have distinctive features which contain traditional elements. One of the elements of this custom is customary law. In the community of Pakraman Bali Village, there are indigenous people in which customary law applies. This customary law is stated in awig-awig. If we look at the discussion then it is related to the legal structure, of course there is a connection related to that part of the legal system. The legal system in a state can be referred to as a national legal system in which the national legal system has parts or elements that each function and have a relationship, namely between one part and another. Likewise, there are laws that are part of the customary law community where the customary law community is part of the village which is an institution in the state structure. This then becomes an issue of how the position of awig-awig is in the national legal system. This research was conducted through an analysis of legal facts and legal doctrine, namely the theoretical and statutory approaches. This article is the result of research funded by the university, so it is the outcome product of this research. The discussion in this analysis shows that awig-awig is written customary law, while what is generally understood so far is the unwritten law. In addition, the position in national law is recognized because it is the right of the customary law communities in Bali (adat in Pakraman Village, Bali). In addition, of course, awig-awig can be used as a source of material law, which is a social conception that exists in society, some of which are still applicable and some need conformity.